Female flowers first: QTL mapping in eastern black walnut (Juglans nigra L.) identifies a dominant locus for heterodichogamy syntenic with that in Persian walnut (J. regia L.) - Warren Chatwin; Devin Shirley; Jacqueline Lopez; Joseph Sarro; John Carlson; Alison Devault; Mike Pfrender; Ronald Revord; Mark Coggeshall; Jeanne Romero-Severson (Tree Genetics & Genomes, 2023)
Eastern black walnut ( Juglans nigra L.), one of the most valuable timber and veneer trees in North America, provides nut shells with unique industrial uses and nut kernels with distinctive culinary attributes. A mature F 1 full-sib progeny orchard of 248 individuals from the cross of two eastern black walnut cultivars provides a long-term resource for discovering genetic mechanisms controlling life history, quality traits, and stress resistance. The genetic linkage map, constructed with 356 single nucleotide polymorphism (SNP) markers and 62 expressed sequence tag simple sequence repeats (EST-SSRs), is 1645.7 cM in length, distributed across the expected 16 linkage groups. In this first application of QTL mapping in J. nigra , we report QTL for budbreak, peak pistillate bloom, peak staminate bloom, and heterodichogamy. A dominant major QTL for heterodichogamy is reported, the sequence for which is syntenic with the heterodichogamy QTL on chromosome 11 of Persian walnut ( J. regia L.). The mapping population parents are both protogynous, and segregation suggests a Mendelian component, with a 3:1-like inheritance pattern from heterozygous parents. Mapping the sequenced EST-SSR markers to the J. regia “Chandler” V2.0 genome sequence revealed evidence for collinearity and structural changes on two of the sixteen chromosomes. The inclusion of sequenced EST-SSR markers enables the direct comparison of this and subsequent J. nigra maps and other Juglandaceae genetic maps. This investigation initiates long-term QTL detection studies for quality and stress resistance traits in black walnut.

Escaping the fate of Sisyphus: assessing resistome hybridization baits for antimicrobial resistance gene capture - Megan S. Beaudry; Jesse C. Thomas; Rodrigo P. Baptista; Amanda H. Sullivan; William Norfolk; Alison Devault; Jacob Enk; Troy J. Kieran; Olin E. Rhodes; K. Allison Perry‐Dow; Laura J. Rose; Natalia J. Bayona‐Vásquez; et al. (Environmental Microbiology, 2021)
Summary Finding, characterizing and monitoring reservoirs for antimicrobial resistance (AMR) is vital to protecting public health. Hybridization capture baits are an accurate, sensitive and cost‐effective technique used to enrich and characterize DNA sequences of interest, including antimicrobial resistance genes (ARGs), in complex environmental samples. We demonstrate the continued utility of a set of 19 933 hybridization capture baits designed from the Comprehensive Antibiotic Resistance Database (CARD)v1.1.2 and Pathogenicity Island Database (PAIDB)v2.0, targeting 3565 unique nucleotide sequences that confer resistance. We demonstrate the efficiency of our bait set on a custom‐made resistance mock community and complex environmental samples to increase the proportion of on‐target reads as much as >200‐fold. However, keeping pace with newly discovered ARGs poses a challenge when studying AMR, because novel ARGs are continually being identified and would not be included in bait sets designed prior to discovery. We provide imperative information on how our bait set performs against CARDv3.3.1, as well as a generalizable approach for deciding when and how to update hybridization capture bait sets. This research encapsulates the full life cycle of baits for hybridization capture of the resistome from design and validation (both in silico and in vitro ) to utilization and forecasting updates and retirement.